Management of Chronic Gout : An Update - Dutta, Asok Kumar (Journal of Chittagong Medical College Teachers' Association, 2012)
Patients who develop chronic gout usually are those whose hyperuricemia is not controlled. It is a persistent disorder of purine metabolism, characterized by abnormally high levels of serum uric acid and attacks of arthritis, with deposits of urates in the joints for chronic gout. Some dietary restriction & pharmacological agents like allopurinol, probenacid, colcicine can be tried with variable success. Febuxostat, a novel nonpurine selective inhibitor of both the oxidized and reduced forms of xanthine oxidase recently marketed in our country, was approved in February 2009 by the US Food and Drug Administration for the management of hyperuricemia in adults with gout. The purpose of this review was to summarize available information about the dietary restriction and therapeutic strategies for management of recurrent and chronic gout with an emphasis on comparison between Febuxatat and Allopurinol with respect to efficacy and safety. JCMCTA 2011; 22(2): 7-11